2023
DOI: 10.3390/antibiotics12020255
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Surveillance of Antimicrobial Resistance among Gram-Negative Bacteria Isolated from Bloodstream Infections in Ghana

Abstract: Background: Antimicrobial resistance (AMR) in Gram-negative bacteria-causing bloodstream infections (BSIs), such as Klebsiella pneumoniae and non-typhoidal Salmonella (NTS), is a major public health concern. Nonetheless, AMR surveillance remains scarce in sub-Saharan Africa, where BSI treatment is largely empirical. The aim of the study was to determine the distribution and AMR patterns of BSI-causing NTS, K. pneumoniae, and other Gram-negative bacteria in Ghana. Methods: A cross-sectional study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…However, while the pooled prevalence provides a useful estimate of ESBL carriage across Africa, individual studies may reveal variations and provide more localised data because the prevalence of ESBL carriage varies widely between different countries, regions, and populations. For example, the ESBL faecal carriage prevalence in our current study is significantly lower than the ESBL levels reported for other patient hosts in Ghana by Obeng-Nkrumah et al in 2013 (49.3%; n = 148/300), 1 Feglo et al in 2013 (48.4%, n = 77/159), 24 Feglo and Adu-Sarkodie in 2016 (57.8%, n = 234/405), 25 Falgenhauer et al in 2019 (61%, n = 33/54), 26 Donkor et al in 2022 (44.6%, n = 145/334), 27 and Mahazu et al in 2022 (62.2%, n = 102/164). 28 It is worth noting that variations in study populations can also influence ESBL carriage rates.…”
Section: Discussionmentioning
confidence: 98%
“…However, while the pooled prevalence provides a useful estimate of ESBL carriage across Africa, individual studies may reveal variations and provide more localised data because the prevalence of ESBL carriage varies widely between different countries, regions, and populations. For example, the ESBL faecal carriage prevalence in our current study is significantly lower than the ESBL levels reported for other patient hosts in Ghana by Obeng-Nkrumah et al in 2013 (49.3%; n = 148/300), 1 Feglo et al in 2013 (48.4%, n = 77/159), 24 Feglo and Adu-Sarkodie in 2016 (57.8%, n = 234/405), 25 Falgenhauer et al in 2019 (61%, n = 33/54), 26 Donkor et al in 2022 (44.6%, n = 145/334), 27 and Mahazu et al in 2022 (62.2%, n = 102/164). 28 It is worth noting that variations in study populations can also influence ESBL carriage rates.…”
Section: Discussionmentioning
confidence: 98%
“…We also believed it was necessary to evaluate the barriers and facilitators of ASPs among hospital in Ghana to guide policies and strategies toward achieving the Ghana NAP goals to fight the rising rate of AMR and its impact on the healthcare system. [43][44][45][46] With respect to the 7 core elements of implementing sustainable ASPs. 15,21 leadership commitment emphasizes the necessity of a health facility having dedicated time, financial and human resources as well as prioritizing AMS activities to enhance appropriate antibiotic use.…”
Section: Discussionmentioning
confidence: 99%
“…We also believed it was necessary to evaluate the barriers and facilitators of ASPs among hospital in Ghana to guide policies and strategies toward achieving the Ghana NAP goals to fight the rising rate of AMR and its impact on the healthcare system. 43 - 46 …”
Section: Discussionmentioning
confidence: 99%
“…Treatment of infections is now hampered by a sustained high prevalence of multidrug resistance among circulating bacterial strains [ 1 – 14 ]. Infection with antibiotic resistant bacteria, such as multidrug resistant (MDR) Mycobacterium tuberculosis , vancomycin-resistant enterococci, and methicillin-resistant Staphylococcus aureus (MRSA), exert broad-ranged impacts that transcend health [ 15 19 ].…”
Section: Introductionmentioning
confidence: 99%